WHY IS ENGLISH HARD TO READ? SURVEY ON ELEMENTARY STUDENTS’ READING DIFFICULTIES - Wijiastuti, P L; Dwi Purbowati
The research aims to find out what difficulties students experience when reading English texts and factors causing difficulty in reading English texts. The type of research is quantitative with survey methods. The total population was 31 students, sampling used total sampling, with a total sample of 31 students. This research was carried out at MI Nurul Islam Penawangan in December-May 2023. Data collection techniques used a questionnaire totaling 10 indicators with 24 statement items, interviews collected 1 indicator with 7 question items and documentation. Test validity with content validity and construct validity, while reliability is by looking of Cronbach’s alpha value. Data analysis techniques using quantitative descriptive. Based on the research, the results obtained were that: 1) 80.6% of students had difficulty reading English texts, 82% had difficulty understanding the contents of English texts, 96.8% had difficulty retelling the contents of English texts; 2) Internal factors causing difficulty in reading English texts are boredom while studying (86.6%), difficulty in pronunciation (82%), difficulty in vocabulary (96.8%) and difficulty understanding grammar (96.8%). Apart from that, external factors that cause students to have difficulty reading English texts are learning media (29.0%), inadequate supporting infrastructure (12.9%), and students studying at home (22.6%).